2003
DOI: 10.1038/sj.cgt.7700644
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-mediated PTEN treatment combined with caffeine produces a synergistic therapeutic effect in colorectal cancer cells

Abstract: The tumor suppressor phosphatase and tensin homologue deleted from chromosome 10 (PTEN) gene is a negative regulator of the phosphatidylinositol-3-kinase (PI3K)/protein kinase B (Akt/PKB) signaling pathway. Overexpression of PTEN in cancer cells results in cell-cycle arrest and cell death through inhibition of PI3K. Caffeine, a xanthine analogue, is well known to enhance the cytocidal and growth-inhibitory effects of DNA-damaging agents such as radiation, UV light, and anticancer agents on tumor cells by abrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 34 publications
3
23
0
Order By: Relevance
“…However, the complete inhibition of PTEN did not totally block the apoptosis in CR cancer cells, so the actual mechanism by which EF24 contributes to the outcome of PTEN activation and apoptosis in cancer cells requires further investigation. This result is consistent with previous reports that up-regulation of PTEN expression blocked cancer cell proliferation and induced apoptosis (34,47,48). On the basis of these results, we hypothesized that the inhibition of cell proliferation and induction of apoptosis in CR human ovarian cancer cells are associated with PTEN expression caused by EF24.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, the complete inhibition of PTEN did not totally block the apoptosis in CR cancer cells, so the actual mechanism by which EF24 contributes to the outcome of PTEN activation and apoptosis in cancer cells requires further investigation. This result is consistent with previous reports that up-regulation of PTEN expression blocked cancer cell proliferation and induced apoptosis (34,47,48). On the basis of these results, we hypothesized that the inhibition of cell proliferation and induction of apoptosis in CR human ovarian cancer cells are associated with PTEN expression caused by EF24.…”
Section: Discussionsupporting
confidence: 82%
“…Further work is required to determine the feasibility of PTEN activation as an adjuvant therapy for human ovarian can- cer. While, to our knowledge, no clinical trial has yet evaluated the effects of PTEN activation by anticancer drugs, some studies using nude mouse xenografts of human tumors have established that PTEN induction results in reduced tumor metastases, tumor regression, and most importantly, the induction of apoptosis (33,47,49).…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, our previous results showed that overexpression of PTEN enhanced intestinal cell differentiation (6). Overexpression of PTEN in colorectal cancer cells resulted in cell cycle arrest and enhanced cell death through inhibition of PI3K (40). Our observation that the blockade of the JNK pathway by pharmacologic (i.e., SP600125) or genetic (i.e., transfection with JNK siRNA) mechanisms attenuated NaBT induction of PTEN strongly argues for a functional role for JNK activation in PTEN induction in intestinal cells.…”
Section: Discussionsupporting
confidence: 69%
“…Our ability to increase PTEN protein level in mouse lung may have significant functional consequences. For example, overexpression of PTEN in cancer cells results in cell cycle arrest and cell death through the inhibition of PI3k (34). Another recent study demonstrated that inhibition of PI3k drastically reduced the invasive capacity of bladder cancer (35).…”
Section: Discussionmentioning
confidence: 99%